Weight Loss Surgery Utilization in Patients Aged 14–25 With Severe Obesity Among Several Healthcare Institutions in the United States - Campoverde Reyes, Karen J.; Misra, Madhusmita; Lee, Hang; Stanford, Fatima Cody (Frontiers in Pediatrics, 2018)
Introduction: Obesity is associated with early co-morbidities and higher mortality. Even though weight loss surgery (WLS) in adolescents with severe obesity reliably achieves safe and lasting improvement in BMI and superior resolution of comorbid diseases, its utilization among young patients in the clinical practice stands unclear. Objective: To show the prevalence of weight loss surgery utilization rates in adolescents and young adults among several healthcare institutions in the United States. Method: WLS in 14-25 years old between 2000 and 2017 was obtained from Washington University, Morehouse Medical, University of Texas, Wake Forest Baptist Medical Center, Beth Israel Deaconess Medical Center, Boston Children's Hospital, Boston Medical Center, and Partners Healthcare using the Shared Health Research Information Network (SHRINE) and Research Patient Data Registry (RPDR) web-based query tools. ICD-9 codes were used for bariatric surgery. Results: Among 2500635 individuals, 18008 (0.7%) had severe obesity. At Partners, 1879 patients had severe obesity, of which 404 (21.5%) underwent WLS, whereas at Washington University, 44 (2.5%) of 1788 the underwent WLS. 13 (2.3%) of the 575 at BIDMC, 43 (1.5%) of the 2969 at BMC, and 37 (0.4%) of 8908 at BCH underwent WLS (p <0.0001 for all). Discussion: Even though WLS has shown to be the most effective to create sustainable changes in metabolic derangements for moderate to severe obesity and its comorbidities, it has been underutilized. Further studies need to be conducted to ensure WLS is utilized for those patients who would achieve the most benefit.